A study of adhesion between hydraulic mortars and concrete - Aguiar, J. L. Barroso de (1998)
Knowledge of the adhesion properties of materials is necessary for many applications. When one has to cover a wall or a concrete pavement with mortar, it is necessary to pay attention to the adhesion between the two materials, otherwise one can have some problems such as the delamination of the two materials after application. We present here a study of the adhesion between hydraulic mortars and concrete. Mortars with permeability-reducing admixtures were used. This type of mortar is used to reduce the possibility of water infiltration in construction. Mortars should be impermeable but this should not affect the adhesion. To measure the adhesion, we used the pull-off test. The results show a decrease in the adhesion strength with increasing permeability-reducing admixture dosage, except for one of the admixtures used. We believe that this result is a consequence of the decrease in porosity caused by the use of a more waterproofing admixture and that a higher dosage contributes to the increase of admixture at the interface. To confirm this, we performed a microscopic analysis of the failure surfaces of the mortars. The decrease in porosity was well seen in this analysis. However, this characteristic of mortars is not the only one that affects adhesion. The composition of the admixture is very important as we found different adhesion strengths, for similar porosity, with different admixtures.